Innovative approach for rapeseed straw recycling using black solider fly larvae: Towards enhanced energy recovery. (April 2022) - Elsayed, Mahdy; Li, Wu; Abdalla, Nashwa S.; Ai, Ping; Zhang, Yanlin; Abomohra, Abd El-Fatah
Abstract: The present study evaluated bio-recycling of rapeseed straw (RS) mixed in different ratios with chicken manure using black soldier fly larvae (BSFL) followed by biodiesel and protein production as an innovative waste management and biorefinery route. Among different treatments, 20% RS ratio showed high fiber biodegradation with enhanced larval biomass yield and lipid accumulation. The average larval development time on the chicken manure was 18.3 days, which significantly reduced to 14.0 days using 20% RS. In addition, application of 20% RS significantly enhanced the survival rate, with higher conversion efficiency comparing to the control. Interestingly, saturated fatty acids content of the produced biodiesel at 20% RS was much higher than that reported for the biodiesel produced currently from rapeseed oil, which resulted in higher cetane number. Based on the current biodiesel industry from rapeseed oil, 1 ha of rapeseed produces 4.2 tons of dry RS annually, that can be converted to 689.4 kg ha −1 of biodiesel using BSFL. In addition, the potential application of BSFL technology could reduce CO2 emissions by 10.42 tons ha −1 . In conclusion, this study suggests BSFL as a promising mini-livestock for innovative RS management through indirect conversion of lignocelluloses into biodiesel. Graphical abstract: Image 1